The Future of Membrane Separation Processes: A Prospective Analysis - Favre, Eric (Frontiers in Chemical Engineering, 2022)
Membrane processes are today one of the key technologies for industrial separations and are expected to play an important role in future sustainable production systems. The combination of materials science and process engineering has historically always been an essential condition to the development of new applications for membranes. The recent development of high performance nanostructured materials, together with new production technologies (such as 3D printing) and high performance computing possibilities is expected to open new horizons to membrane processes. The different challenges and prospects to be addressed to achieve this purpose are discussed, with an emphasis on the future of process industries in terms of feedstocks, energy sources, and environmental impact.